2021
DOI: 10.3390/sym13050839
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Hybrid Fuzzy MCGDM Methodologies for Optimal Robot Selection Process

Abstract: The generalized interval-valued trapezoidal fuzzy best-worst method (GITrF-BWM) provides more reliable and more consistent criteria weights for multiple criteria group decision making (MCGDM) problems. In this study, GITrF-BWM is integrated with the extended TOPSIS (technique for order preference by similarity to the ideal solution) and extended VIKOR (visekriterijumska optimizacija i kompromisno resenje) methods for the selection of the optimal industrial robot using fuzzy information. For a criteria-based se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 51 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Hornakova et al [48] confirmed that mobile robots are the best equipment for material handling in an industrial setting. Rashid et al [49] integrated the generalized interval-valued trapezoidal fuzzy bestworst method with extended TOPSIS and extended VIKOR for the selection of the optimal industrial robot, while concluding that extended TOPSIS is more stable than extended VIKOR after testing the reliability and stability of both methods through sensitivity analysis. Rashid et al [50] developed a hybrid MCDM methodology to select the best industrial robot alternatives by combining the BWM and EDAS method, followed by sensitivity analysis, and compared to other distance-based approaches, such as VIKOR and TOPSIS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hornakova et al [48] confirmed that mobile robots are the best equipment for material handling in an industrial setting. Rashid et al [49] integrated the generalized interval-valued trapezoidal fuzzy bestworst method with extended TOPSIS and extended VIKOR for the selection of the optimal industrial robot, while concluding that extended TOPSIS is more stable than extended VIKOR after testing the reliability and stability of both methods through sensitivity analysis. Rashid et al [50] developed a hybrid MCDM methodology to select the best industrial robot alternatives by combining the BWM and EDAS method, followed by sensitivity analysis, and compared to other distance-based approaches, such as VIKOR and TOPSIS.…”
Section: Literature Reviewmentioning
confidence: 99%